A degradable heat-sealing adhesive emulsion and a composite aluminum foil for biomedical packaging
By using easy-degradable heat sealant latex in the heat sealant layer of composite aluminum foil, and using two methods of microbial enzyme decomposition and photodegradation, the problem of poor degradation performance of the heat sealant layer in the prior art is solved, and a better degradation effect is achieved.
Patent Information
- Application Number
- CN202310046940.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-01-31
AI Technical Summary
The composite aluminum foil heat sealant layer in existing pharmaceutical packaging has poor degradation performance in natural environments.
The degradation of the heat sealing layer is promoted by using an easy-to-degradation heat sealing latex composed of an organic zirconium crosslinking agent, starch, acrylamide copolymer and heat sealing latex.
The degradation performance of the heat sealant layer in the natural environment has been significantly improved, and the degradation capacity of the composite aluminum foil in biomedical packaging has also been improved.
Smart Images

Figure BDA0004055936660000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite aluminum foil, and more specifically, to a degradable heat-sealing adhesive latex and a composite aluminum foil for biomedical packaging. Background Art
[0002] Aluminum foil is an extremely thin sheet formed by multiple calendering of high-purity aluminum. It is an excellent thermal conductor and light-shielding body, with good mechanical strength, light weight, no thermal adhesion, metallic luster, good light-shielding properties, strong light reflection ability, not easy to be corroded, good barrier properties, moisture-proof and waterproof, and strong airtightness. Heat-sealing adhesive emulsion is usually used for coating of aluminum foil as the heat-sealing layer of aluminum foil. Therefore, composite aluminum foil can be seen everywhere in life and is often used in biomedical packaging.
[0003] In the related art, a Chinese application document with application number CN108656684A discloses a composite aluminum foil for biopharmaceutical packaging, including a PVC layer, an aluminum foil layer, a CPP layer, an anti-tear buffer layer, a heat-sealing adhesive layer and a PET layer, wherein the PVC layer, the aluminum foil layer, the CPP layer, the anti-tear buffer layer, the heat-sealing adhesive layer and the PET layer are adjacently connected together from the inside to the outside; wherein the anti-tear buffer layer is a polyurethane resin layer, and the heat-sealing adhesive layer is coated with a heat-sealing adhesive latex.
[0004] With respect to the above-mentioned related technologies, the heat-sealing adhesive layer formed by coating the heat-sealing adhesive latex in the composite aluminum foil of the above-mentioned medical packaging has poor degradation performance in the natural environment. Summary of the invention
[0005] In order to provide a heat-sealing adhesive layer with good degradation performance, the present application provides an easily degradable heat-sealing adhesive emulsion and a composite aluminum foil for biomedical packaging.
[0006] In the first aspect, the present application provides a degradable heat-sealing latex, which adopts the following technical solution:
[0007] A degradable heat-sealing adhesive latex is prepared from the following raw materials in parts by weight: 5-10 parts of an organic zirconium cross-linking agent, 20-40 parts of an acrylamide copolymer, 10-20 parts of starch and 50-70 parts of a heat-sealing adhesive latex.
[0008] By adopting the above technical scheme, starch itself, as a biodegradable agent, is first decomposed by enzymes released by microorganisms, making the plastic products porous and increasing the specific surface area, which is conducive to further enzymatic hydrolysis or natural decomposition; zirconium chelates and compound products can be used as photodegradants, which can decompose the hydroperoxides in the heat-sealing latex into free radicals, accelerating the degradation of the heat-sealing latex. This application uses acrylamide copolymers to connect starch with an organic zirconium cross-linking agent. On the one hand, it allows two different types of degradation agents to cooperate with each other, and two degradation methods are used at the same site to jointly promote the degradation of the heat-sealing latex, so that the degradation performance of the heat-sealing latex in nature is better; on the other hand, acrylamide copolymers can also act as a part of the heat-sealing latex in the heat-sealing latex, saving the raw materials of the heat-sealing latex.
[0009] Optionally, the starch is one or more of corn starch, sweet potato starch, wheat starch, mung bean starch, water chestnut starch, lotus root starch and water chestnut starch.
[0010] By adopting the above technical scheme, the starches used as biodegradable agents are all cheap and readily available starches in daily life, and are non-toxic and will not cause environmental pollution when volatilized in the natural environment. Therefore, the above starches are selected as a component in the easily degradable heat-sealing adhesive latex, which is conducive to promotion and application.
[0011] Optionally, the acrylamide copolymer is anionic polyacrylamide or cationic polyacrylamide.
[0012] By adopting the above technical scheme, anionic polyacrylamide and cationic polyacrylamide can not only be connected with starch and organic zirconium cross-linking agent through amide groups; but also can further tightly connect starch and organic zirconium cross-linking agent through electrostatic attraction through the action of anions and cations. Finally, after being mixed with the heat-sealing adhesive latex, two degradation methods can be used at a single site of the heat-sealing adhesive latex to simultaneously degrade, and the degradation effect is good.
[0013] Optionally, the method for preparing the easily degradable heat-sealing adhesive emulsion comprises the following steps:
[0014] Step 1, starch and acrylamide copolymer are mixed with water, and stirred at 30-50° C. to obtain modified starch;
[0015] Step 2, mixing the modified starch with the organic zirconium cross-linking agent, and stirring at room temperature to obtain a composite degradation agent;
[0016] Step 3, mixing the compound degradation agent with the heat sealing adhesive latex to obtain an easily degradable heat sealing adhesive latex.
[0017] By adopting the above technical scheme, the purpose of step 1 is to first connect starch with acrylamide copolymer; the purpose of step 2 is to connect the modified starch with the organic zirconium cross-linking agent; the reasons for the step-by-step process are two aspects. On the one hand, it is to avoid excessive physical combination of starch and organic zirconium cross-linking agent, and physical combination is not as strong as chemical combination. In step 3, when the compound degradation agent is mixed with the heat-sealing adhesive, mechanical stirring may separate the physically combined starch and organic zirconium cross-linking agent; on the other hand, the organic zirconium cross-linking agent, acrylamide copolymer and starch are wrapped step by step, so that during the initial degradation, a large amount of organic zirconium cross-linking agent and a small amount of starch cooperate; during the later degradation, a large amount of starch and a small amount of organic zirconium cross-linking agent cooperate; the organic zirconium cross-linking agent and starch promote the degradation of the easily degradable heat-sealing adhesive emulsion step by step, and the degradation time is long; the degradation effect of the easily degradable heat-sealing adhesive emulsion prepared by the step-by-step combination method of the present application is better.
[0018] Optionally, after stirring at room temperature, step 2 further comprises the steps of reduced pressure filtration and drying to finally obtain a composite degradation agent.
[0019] By adopting the above technical solution, the purpose of the reduced pressure filtration is to remove excess water in the compound degradation agent and improve the bonding performance of the finally obtained easily degradable heat-sealing adhesive latex.
[0020] In a second aspect, the present application provides a composite aluminum foil for biopharmaceutical packaging, which adopts the following technical solution: a composite aluminum foil for biopharmaceutical packaging, comprising an aluminum foil layer and a heat-sealing adhesive layer made from the above-mentioned easily degradable heat-sealing adhesive emulsion.
[0021] By adopting the above technical solution, the heat seal adhesive layer made by the above easily degradable heat seal adhesive emulsion is combined with the aluminum foil layer, which can accelerate the degradation of the aluminum foil layer, thereby improving the degradation capacity of the composite aluminum foil for biomedical packaging.
[0022] Optionally, the thickness of the heat-sealing adhesive layer is 0.1-0.8 μm.
[0023] By adopting the above technical solution, a heat-sealing adhesive layer with a certain thickness can not only play the role of a heat-sealing adhesive, but also effectively promote the degradation of the composite aluminum foil of the biomedical packaging.
[0024] Optionally, it also includes a PVC layer, a CPP layer, a tear-resistant buffer layer and a PET layer.
[0025] By adopting the above technical scheme, the PVC layer, CPP layer, tear-resistant buffer layer and PET layer are added to the composite aluminum foil for biomedical packaging, which not only can encapsulate the aluminum foil layer to avoid the contamination of chlorine in the aluminum foil layer, but also can enhance the various mechanical properties of the composite aluminum foil for biomedical packaging.
[0026] Optionally, the composite aluminum foil of the biopharmaceutical packaging is made by sequentially connecting a PVC layer, an aluminum foil layer, a CPP layer, an anti-tear buffer layer, a heat-sealing adhesive layer and a PET layer.
[0027] By adopting the above technical scheme, a tear-resistant buffer layer and a heat-sealing adhesive layer are provided between the PET layer and the aluminum foil layer, so it can be ensured that the medicine will not be contaminated by the chlorine element in the aluminum foil. Since the tear-resistant buffer layer can effectively prevent the damage of the medicine packaging, the safety performance of the composite aluminum foil for biomedical packaging is higher. When the heat-sealing adhesive layer located in the middle layer is degraded, it can promote the degradation of the composite aluminum foil of the entire biomedical packaging.
[0028] In summary, this application has the following beneficial effects:
[0029] 1. The present application uses acrylamide copolymers to connect starch and organic zirconium crosslinking agents. On the one hand, the two different types of degradation agents can cooperate with each other, and two degradation methods are used at the same site to jointly promote the degradation of the heat-sealing adhesive emulsion; on the other hand, the acrylamide copolymer can also serve as a part of the heat-sealing adhesive in the heat-sealing adhesive emulsion;
[0030] 2. The present application uses anionic polyacrylamide and cationic polyacrylamide, which can not only connect with starch and organic zirconium crosslinking agent through amide groups, but also can closely connect starch and organic zirconium crosslinking agent through electrostatic attraction through the action of anions and cations. Finally, after mixing with heat-sealing adhesive latex, two degradation methods can be used at a single site of the heat-sealing adhesive latex to degrade simultaneously, with good degradation effect and long duration of degradation promotion;
[0031] 3. In the composite aluminum foil of biomedical packaging, the heat-sealing adhesive layer is located in the middle layer. When the heat-sealing adhesive layer degrades, it can promote the degradation of the composite aluminum foil of the entire biomedical packaging. DETAILED DESCRIPTION
[0032] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0033] The sources of raw materials of the following embodiments and comparative examples are provided: the raw materials of the embodiments and comparative examples can be purchased commercially, the molecular weight of anionic polyacrylamide is 10 million; the molecular weight of cationic polyacrylamide is 10 million; the molecular weight of nonionic polyacrylamide is 10 million; the organic zirconium crosslinking agent is Dovkaite Tyzor212; the heat sealing adhesive emulsion is EAA emulsion, model, E-532.
[0034] An embodiment of a degradable heat seal latex
[0035] Example 1
[0036] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0037] Step 1, 10 g of wheat starch, 40 g of anionic polyacrylamide and 40 g of water were mixed, and stirred at 1000 rpm for 1 h at 50° C. to obtain modified starch;
[0038] Step 2, mixing the modified starch with 5g of an organic zirconium crosslinking agent, stirring at a speed of 1000rpm for 40min at room temperature to obtain a preliminary compound degradation agent; filtering the preliminary compound degradation agent under reduced pressure, and then drying it to a solid powder to obtain a compound degradation agent; Step 3, mixing the compound degradation agent with 70g of a heat-sealing adhesive latex, stirring at a speed of 1000rpm for 20min at room temperature to obtain an easily degradable heat-sealing adhesive latex.
[0039] A degradable heat-sealing adhesive latex is applied to a composite aluminum foil for biomedical packaging; a composite aluminum foil for biomedical packaging comprises a PVC layer, an aluminum foil layer, a CPP layer, an anti-tear buffer layer, a heat-sealing adhesive layer and a PET layer, wherein the PVC layer, the aluminum foil layer, the CPP layer, the anti-tear buffer layer, the heat-sealing adhesive layer and the PET layer are heat-sealed in sequence, and the heat-sealing adhesive layer is formed by coating the degradable heat-sealing adhesive latex on the anti-tear buffer layer, and is cured at 50°C for 1 hour; wherein the thickness of the PVC layer is 1 μm, the thickness of the aluminum foil layer is 0.8 μm, the thickness of the CPP layer is 0.6 μm, the anti-tear buffer layer is a polyurethane resin layer, the thickness of the anti-tear buffer layer is 0.2 μm, the thickness of the heat-sealing adhesive layer is 0.3 μm, and the thickness of the PET layer is 0.5 μm.
[0040] Example 2
[0041] The difference from Example 1 is that the amount of raw materials added in the preparation method of the easily degradable heat-sealing adhesive latex is different, and the specific steps are as follows;
[0042] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0043] Step 1, 20 g of wheat starch, 20 g of anionic polyacrylamide and 40 g of water were mixed, and stirred at 1000 rpm for 1 h at 30° C. to obtain modified starch;
[0044] Step 2, mixing the modified starch with 10g of an organic zirconium crosslinking agent, stirring at a speed of 1000rpm for 40min at room temperature to obtain a preliminary compound degradation agent; filtering the preliminary compound degradation agent under reduced pressure, and then drying it to a solid powder to obtain a compound degradation agent; Step 3, mixing the compound degradation agent with 50g of a heat-sealing adhesive latex, stirring at a speed of 1000rpm for 20min at room temperature to obtain an easily degradable heat-sealing adhesive latex.
[0045] Example 3
[0046] The difference from Example 1 is that the amount of raw materials added in the preparation method of the easily degradable heat-sealing adhesive latex is different, and the specific steps are as follows;
[0047] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0048] Step 1, 15 g wheat starch, 30 g anionic polyacrylamide and 40 g water were mixed, and stirred at 1000 rpm for 1 h at 38° C. to obtain modified starch;
[0049] Step 2, mixing the modified starch with 8g of an organic zirconium crosslinking agent, stirring at a speed of 1000rpm for 40min at room temperature to obtain a preliminary compound degradation agent; filtering the preliminary compound degradation agent under reduced pressure, and then drying it to a solid powder to obtain a compound degradation agent; Step 3, mixing the compound degradation agent with 60g of a heat-sealing adhesive latex, stirring at a speed of 1000rpm for 20min at room temperature to obtain an easily degradable heat-sealing adhesive latex.
[0050] Example 4
[0051] The difference from Example 3 is that the anionic polyacrylamide in Example 3 is replaced by an equal weight of cationic polyacrylamide.
[0052] Example 5
[0053] The difference from Example 3 is that the anionic polyacrylamide in Example 3 is replaced by an equal weight of nonionic polyacrylamide.
[0054] Example 6
[0055] The difference from Example 3 is that the wheat starch in Example 3 is replaced by lotus root starch and mung bean starch in equal weights, wherein the weight ratio of lotus root starch to mung bean starch is 1:1.
[0056] Example 7
[0057] The difference from Example 3 is that the preparation steps are different, and the specific steps are as follows:
[0058] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0059] Step 1, 15 g of wheat starch, 8 g of an organic zirconium crosslinking agent and 40 g of water were mixed, and stirred at 1000 rpm for 1 h at 38° C. to obtain modified starch;
[0060] Step 2, mixing the modified starch with 30 g of anionic polyacrylamide, stirring at 1000 rpm for 40 min at room temperature to obtain a preliminary compound degradation agent; filtering the preliminary compound degradation agent under reduced pressure, and then drying it to a solid powder to obtain a compound degradation agent;
[0061] Step 3, mixing the compound degradation agent with 60 g of the heat-sealing adhesive latex, stirring at room temperature at a speed of 1000 rpm for 20 min, to obtain an easily degradable heat-sealing adhesive latex.
[0062] Example 8
[0063] The difference from Example 3 is that the preparation steps are different, and the specific steps are as follows:
[0064] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0065] Step 1, 15g of wheat starch, 8g of organic zirconium crosslinking agent, 30g of anionic polyacrylamide and 40g of water are mixed, and stirred at 1000rpm for 1h at 38°C to obtain a preliminary compound degradation agent; the preliminary compound degradation agent is filtered under reduced pressure, and then dried to a solid powder to obtain a compound degradation agent;
[0066] Step 2: Mix the compound degradation agent with 60 g of the heat-sealing adhesive latex, and stir at room temperature at a speed of 1000 rpm for 20 minutes to obtain an easily degradable heat-sealing adhesive latex.
[0067] Example 9
[0068] The difference from Example 3 is that the preparation steps are different, and the specific steps are as follows:
[0069] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0070] Step 1, 15g wheat starch, 8g organic zirconium crosslinking agent, 30g anionic polyacrylamide and 60g heat sealing adhesive latex are mixed, and stirred at 500rpm for 1.5h at 38°C under sealing conditions to obtain a degradable heat sealing adhesive latex.
[0071] Comparative Example 1
[0072] The difference from Example 3 is that the amount of raw materials of the easily degradable heat-sealing adhesive latex is different. The specific steps are as follows;
[0073] A method for preparing a degradable heat-sealing adhesive latex comprises the following steps:
[0074] Step 1, 5 g of wheat starch, 50 g of anionic polyacrylamide and 40 g of water were mixed, and stirred at 1000 rpm for 1 h at 38° C. to obtain modified starch;
[0075] Step 2, mixing the modified starch with 3g of an organic zirconium crosslinking agent, stirring at a speed of 1000rpm for 40min at room temperature to obtain a preliminary compound degradation agent; filtering the preliminary compound degradation agent under reduced pressure, and then drying it to a solid powder to obtain a compound degradation agent; Step 3, mixing the compound degradation agent with 80g of a heat-sealing adhesive latex, stirring at a speed of 1000rpm for 20min at room temperature to obtain an easily degradable heat-sealing adhesive latex.
[0076] Comparative Example 2
[0077] The difference from Example 3 is that no anionic polyacrylamide is added.
[0078] Comparative Example 3
[0079] The difference from Example 3 is that no wheat starch is added, and 23 g of an organic zirconium cross-linking agent is added.
[0080] Comparative Example 4
[0081] The difference from Example 3 is that no organic zirconium cross-linking agent is added, and 23 g of wheat starch is added.
[0082] Comparative Example 5
[0083] The difference from Example 3 is that a commercially available heat-sealing adhesive emulsion, EAA emulsion, model number, E-532, is used.
[0084] Performance testing
[0085] The easily degradable heat-sealing adhesive latex prepared in Examples 1 to 9 and Comparative Examples 1 to 5 was coated on an aluminum foil sheet, the thickness of the aluminum foil sheet was 0.8 μm, the thickness of the heat-sealing adhesive layer was 0.3 μm, and it was cured at 50° C. for 1 hour; the degradation rate and water contact angle were tested, and the test results are shown in Table 1; the composite aluminum foil for biomedical packaging prepared in Example 3, Comparative Example 2, and Comparative Example 5 was subjected to performance testing, and the 8-week degradation rate, water contact angle and 16-week degradation rate, water contact angle were tested; the test results are shown in Table 2;
[0086] Testing method Testing environment: Soil 5-10cm deep underground at Shanghai Xingji Industrial Waste Treatment Co., Ltd.; placed under natural sunlight, water was added every day to keep the soil humidity at the initial humidity;
[0087] Degradation rate: The aluminum foil coated with the heat-sealing adhesive layer was placed in the above-mentioned test environment, shaken at 180 rpm and 28°C for 8 weeks, then taken out and placed in a sterile centrifuge tube for sterilization, then soaked in 75% ethanol for 3 hours, and ultrasonically cleaned for 30 minutes. After soaking, it was rinsed with sterile water for 3 times, and the water was absorbed with sterile filter paper; Degradation rate (%) = loss mass of the aluminum foil coated with the heat-sealing adhesive layer / mass of the aluminum foil coated with the heat-sealing adhesive layer before shaking × 100%;
[0088] Water contact angle: The degradation experiment was carried out in the same manner as above, and the water contact angle of the aluminum foil coated with the heat-sealing adhesive layer before and after shaking was measured using a water contact angle meter;
[0089] Table 1
[0090] Degradation rate (%) Water contact angle (°) Example 1 14.2±0.14 64.8±0.8 Example 2 14.1±0.07 64.9±1.0 Example 3 14.3±0.05 65.5±1.2 Example 4 14.2±0.06 64.7±0.8 Example 5 13.6±0.1 68.3±0.6 Example 6 14.1±0.08 64.8±0.3 Example 7 11.6±0.09 73.2±0.7 Example 8 11.7±0.12 73.6±0.09 Example 9 9.8±0.1 75.3±0.5 Comparative Example 1 9.6±0.06 75.6±1.2 Comparative Example 2 8.6±0.08 78.6±0.8 Comparative Example 3 6.5±0.09 84.2±1.1 Comparative Example 4 6.3±0.11 86.4±0.7 Comparative Example 5 1.4±0.07 101.3±1.3
[0091] In Examples 1-9 and Comparative Examples 1-5, the water contact angles before shaking were all the same as the water contact angles of the aluminum foil, which were 109.3±1.3°.
[0092] Table 1 Data analysis
[0093] Combining Examples 1, 2 and 3, it can be seen that the difference between Examples 1, 2 and 3 is that the raw material ratios for preparing the easily degradable heat-sealing adhesive emulsion are different, but the prepared easily degradable heat-sealing adhesive emulsion has a higher degradation rate, a smaller water contact angle and a better degradation effect, which proves that the raw material ratios of Examples 1, 2 and 3 are all more appropriate.
[0094] Combining Examples 3, 4 and 5, it can be seen that the difference between Examples 3, 4 and 5 is that anionic polyacrylamide, cationic polyacrylamide and nonionic polyacrylamide are used respectively, and the degradation rate of the easily degradable heat-sealing adhesive emulsion prepared in Examples 3 and 4 is higher, the water contact angle is smaller, and the degradation effect is good; the degradation rate of the degradable heat-sealing adhesive emulsion prepared in Example 5 is lower than that in Examples 3 and 4; it is proved that the effect of the easily degradable heat-sealing adhesive emulsion prepared by nonionic polyacrylamide is worse than that of the easily degradable heat-sealing adhesive emulsion prepared by anionic polyacrylamide and cationic polyacrylamide.
[0095] In combination with Examples 3 and 6, it can be seen that the difference between Examples 3 and 6 is that different types of starch are used, and the easily degradable heat-sealing adhesive emulsions prepared in Examples 3 and 6 have a higher degradation rate, a smaller water contact angle, and a good degradation effect; it is proved that the starches protected by the claims of the present application can be applied to the easily degradable heat-sealing adhesive emulsion of the present application.
[0096] Combining Example 3 with Examples 7, 8, and 9, it can be seen that the difference between Examples 7, 8, and 9 is that the steps for preparing the easily degradable heat-sealing adhesive emulsion are different. Example 3 first forms modified starch, then forms a compound degradation agent with an organic zirconium cross-linking agent, and uses the compound degradation agent to prepare the easily degradable heat-sealing adhesive emulsion; Example 8 mixes starch with an organic zirconium cross-linking agent, then forms a compound degradation agent, and uses the compound degradation agent to prepare the easily degradable heat-sealing adhesive emulsion; Example 9 mixes all raw materials at the same time to directly form a degradable heat-sealing adhesive emulsion. The degradation rate of the easily degradable heat-sealing adhesive emulsion prepared in Examples 7 and 8 is lower than that of the easily degradable heat-sealing adhesive emulsion prepared in Example 3; the degradation rate of the easily degradable heat-sealing adhesive emulsion prepared in Example 9 is lower than that of the easily degradable heat-sealing adhesive emulsion prepared in Examples 7 and 8; it proves that the steps for preparing the easily degradable heat-sealing adhesive emulsion in this application are very important, and only by following the steps in Example 3 can an easily degradable heat-sealing adhesive emulsion with better degradation effect be prepared.
[0097] Combining Example 3 and Comparative Example 1, it can be seen that compared with Example 3, the raw material ratio of Comparative Example 1 exceeds the protection scope of the present application, and the degradation rate of the easily degradable heat-sealing adhesive emulsion prepared is small and the water contact angle is large.
[0098] Combining Example 3 with Comparative Examples 2, 3, and 4, it can be seen that Comparative Example 2 does not add anionic polyacrylamide; Comparative Example 3 does not add wheat starch, and an organic zirconium cross-linking agent is used instead of wheat starch; Comparative Example 4 does not add an organic zirconium cross-linking agent, and wheat starch is used instead of the organic zirconium cross-linking agent; compared with Example 3, the easily degradable heat-sealing adhesive emulsions prepared in Comparative Examples 2, 3, and 4 have a small degradation rate and a large water contact angle; it is proved that the organic zirconium cross-linking agent, anionic polyacrylamide and wheat starch of the present application synergistically enhance the effect, are indispensable, and cannot replace each other.
[0099] Combining Example 3 and Comparative Example 5, it can be seen that Comparative Example 5 uses commercially available heat-sealing adhesive latex. Compared with Example 3, the easily degradable heat-sealing adhesive latex prepared in Comparative Example 5 has a small degradation rate and a large water contact angle, which proves that the easily degradable heat-sealing adhesive latex of the present application has a good degradation effect.
[0100] Table 2
[0101]
[0102] In Example 3 and Comparative Examples 2 and 5, the water contact angle before shaking is the water contact angle of the PVC layer, which is 113.2±0.9°.
[0103] Table 2 Data analysis
[0104] In combination with Example 3, Comparative Examples 2 and 5, it can be seen that no anionic polyacrylamide is added to the composite aluminum foil for biopharmaceutical packaging in Comparative Example 2; Comparative Example 5 directly uses commercially available heat-sealing adhesive latex to prepare the composite aluminum foil for biopharmaceutical packaging; compared with Example 3, the composite aluminum foil for biopharmaceutical packaging prepared in Comparative Examples 2 and 5 has a small degradation rate and a large water contact angle; it is proved that the composite aluminum foil for biopharmaceutical packaging prepared by the easily degradable heat-sealing adhesive latex of the present application has a good degradation effect.
[0105] The degradation rate of the composite aluminum foil for biopharmaceutical packaging prepared in Example 3 in 16 weeks is twice that of the degradation rate in 8 weeks, and the water contact angle in 16 weeks is also about 10° less than that in 8 weeks, which proves that the degradation effect of the composite aluminum foil for biopharmaceutical packaging of the present application continues from 8 to 16 weeks; while the degradation rate of the composite aluminum foil for biopharmaceutical packaging prepared in Comparative Example 2 decreases slowly, and the water contact angle decreases less, which proves that not adding anionic polyacrylamide has a greater impact on the duration of degradation; the degradation effect of the composite aluminum foil for biopharmaceutical packaging prepared in Comparative Example 5 is almost unchanged from 8 to 16 weeks, which proves that the composite aluminum foil for biopharmaceutical packaging without adding degradable materials is difficult to degrade in the natural environment.
[0106] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A degradable heat-sealing adhesive emulsion, characterized in that: The method is prepared from the following raw materials in parts by weight: 5-10 parts of an organic zirconium crosslinking agent, 20-40 parts of an acrylamide copolymer, 10-20 parts of starch and 50-70 parts of a heat-sealing adhesive latex; The preparation method of the easily degradable heat-sealing adhesive emulsion comprises the following steps: Step 1, starch and acrylamide copolymer are mixed with water, and stirred at 30-50° C. to obtain modified starch; Step 2, mixing the modified starch with the organic zirconium cross-linking agent, and stirring at room temperature to obtain a composite degradation agent; Step 3, mixing the compound degradation agent with the heat sealing adhesive latex to obtain an easily degradable heat sealing adhesive latex.
2. The easily degradable heat-sealing adhesive emulsion according to claim 1, characterized in that: The starch is one or more of corn starch, sweet potato starch, wheat starch, mung bean starch, water chestnut starch, lotus root starch and water chestnut starch.
3. The easily degradable heat-sealing adhesive emulsion according to claim 1, characterized in that: The acrylamide copolymer is anionic polyacrylamide or cationic polyacrylamide.
4. The easily degradable heat-sealing adhesive emulsion according to claim 1, characterized in that: After stirring at room temperature, step 2 further includes the steps of reduced pressure filtration and drying to finally obtain the composite degradation agent.
5. A composite aluminum foil for biomedical packaging, characterized in that: The invention comprises an aluminum foil layer and a heat-sealing adhesive layer made from the easily degradable heat-sealing adhesive emulsion according to any one of claims 1 to 4.
6. The composite aluminum foil for biopharmaceutical packaging according to claim 5, characterized in that: The thickness of the heat-sealing adhesive layer is 0.1-0.8 μm.
7. The composite aluminum foil for biopharmaceutical packaging according to claim 5, characterized in that: It also includes a PVC layer, a CPP layer, a tear-resistant buffer layer and a PET layer.
8. The composite aluminum foil for biopharmaceutical packaging according to claim 7, characterized in that: The composite aluminum foil for biomedical packaging is prepared by sequentially connecting a PVC layer, an aluminum foil layer, a CPP layer, an anti-tearing buffer layer, a heat-sealing adhesive layer and a PET layer.
Citation Information
Patent Citations
Composite aluminum foil for biological medicine packaging
CN108656684A
Stretch-proof and easily-degradable plastic bag and preparation method thereof
CN112457615A